Threatened marine fishes in the Gulf of Guinea. - Abdirahman, H. M.; Saba, A. O.; Lawal, A. A.; Aghogho, K. D.; Aneyo, I.; Badar, I. I.; Bassey, O. P.; Dordzi, B. D.; Glavee, C. C.; Agyapong, D.; Dokuboba, A.; Udoyen, G.; et al. (Coastal Ocean Environment Summer School In Nigeria and Ghana (COESSING), 2023)
We gathered information about the conservation status and the major life history traits (LHTs); Length-Weight Relationship (LWR), Reproduction, Diet of the threatened marine fishes of the Gulf of Guinea . Data were obtained from Fishbase and the IUCN Red List online databases. Out of 24 species, the majority is classified as Vulnerable (N=19; 83%) and the rest as Endangered (N=17%). Criterion A (Population data) has been mainly (N=70%) used as a proxy for the determination of the conservation status. LWR and diet parameters are the most studied LHTs while one out five of the examined species (N=6) have no information regarding the examined LHTs in the online repositories. The most important finding is that the major threats to the species examined are biological resource use (74%), residential and commercial development (30%) along with pollution events (26%).
Keywords: Threatened; Threatened marine fishes; Gulf of Guinea